Efektivitas Pemberian Aromaterapi Lavender Dan Jahe Terhadap Penurunan Frekuensi Mual Muntah Pada Ibu Hamil Trimester I Di BPM Trucuk Klaten - RD Rahayu; Sugita Sugita (Poltekkes Kemenkes Surakarta, 2018)
Abstract: Lavender Aromtherapy, Ginger Aromatherapy, Nausea Vomiting, Pregnant Mother. Aromatherapy is a therapy modality or alternative treatment by using a pure aromatherapy extract in the form of volatile plant fluid material and other aromatherapy compounds from plants. Knowing the Effectiveness of Aromatherapy Lavender and Ginger Aromatherapy on Reduced Frequency of Nausea Vomiting in Trimester Pregnant Mother at BPM Trucuk Klaten. Quantitative type with this research design using quasi experiment (quasi experiment). The population in this study were all trimester I pregnant mother who checked their pregnancy at BPM Trucuk Klaten during may until Juni 2017. The sampling technique is accidental sampling is 32 pregnan. Data analysis using paired t-test and independent t-test.Results. There was a significant difference between mean intensity degree of vomiting before and after ginger aroma therapy with p value = 0,000 (α<0,05). There was a significant difference between mean intensity of degree of nausea of vomiting before and after aromatherapy therapy with p value 0.000 (α <0,05). The scent of lavender therapy is more effective against nausea and vomiting (8.50) than in the ginger aroma therapy group (6.50), so it can be concluded that the aroma of lavender therapy is more effective than the aroma of ginger therapy.